Influence of metabolism-related comorbidities and insulin resistance on new onset of chronic kidney disease in a health check-up population: a two-stage retrospective cohort study - Yang Zhang; Xin Shen; Guang Yang; Ying Ding; Jiahui Zhao; Qingli Cheng; Bokai Cheng; Yansong Zheng (BMJ Open Diabetes Research & Care, 2025)
Introduction Limited research has focused on the prospective influence of insulin resistance (IR) on new-onset chronic kidney disease (CKD) in healthy screening populations. Therefore, we aimed to investigate how IR, assessed via the estimated glucose disposal rate (eGDR), and metabolism-related comorbidities influence new-onset CKD.Research design and methods This two-stage retrospective cohort study (cross-sectional and longitudinal analyses) used data from health check-up participants at the Chinese People’s Liberation Army General Hospital (2009–2021). The cross-sectional analysis included 83 346 participants with or without CKD; the longitudinal analyses included 13 738 participants without prior CKD who visited the hospital at least two times. The cross-sectional phase of this study analyzed the relationship between IR and CKD; the longitudinal phase analyzed the relationship between IR and new-onset CKD. The mediating role of metabolism-related comorbidities was also explored.Results In the cross-sectional analysis, 6.77% (n=5643) of patients had prior CKD. The eGDR was significantly higher in the non-CKD group than in the CKD group (9.16±2.11 vs 7.19±2.32, p<0.001). Higher eGDR was associated with lower CKD prevalence (OR: 0.91, 95% CI: 0.89 to 0.93, P for trend<0.001). In the cohort analysis, the average time to trigger endpoint events was 2.95±2.02 years, with 403 (2.93%) new-onset CKD cases reported. A linear correlation was observed between eGDR and new-onset CKD (p<0.001), with higher eGDR linked to reduced CKD risk (HR: 0.88, 95% CI: 0.82 to 0.96, P for trend=0.002). Mediation analysis revealed significant indirect effects of diabetes mellitus (17.1%), systolic blood pressure (22.0%), glycated hemoglobin (11.1%), and brachial–ankle pulse wave velocity (9.7%) (all p<0.05).Conclusions IR is independently linked to new-onset CKD, with blood glucose, blood pressure, and arterial stiffness mediating this relationship. These findings underscore the importance of managing IR and metabolic comorbidities to prevent CKD onset in at-risk populations.